LINC00586 Represses ASXL1 Expression Thus Inducing Epithelial-To-Mesenchymal Transition of Colorectal Cancer Cells Through LSD1-Mediated H3K4me2 Demethylation - Liu, Fengting; Ma, Xiaofang; Bian, Xiyun; Zhang, Chunyan; Liu, Xiaozhi; Liu, Qiang (Frontiers in Pharmacology, 2022)
Colorectal cancer (CRC) is a major public health problem on a global scale by virtue of its relatively high incidence. The transition of tumor cells from an epithelial to a mesenchymal-like phenotype, so-called epithelial-to-mesenchymal transition (EMT), is a key hallmark of human cancer metastasis, including CRC. Understanding the signaling events that initiate this phenotypic switch may provide opportunities to limit the metastasis of CRC. In this study, we aim to identify long non-coding RNA (lncRNA) mediated epigenetic regulation under the context of CRC. 54 paired samples of tumor tissues and surrounding non-tumor tissues were collected from CRC patients. Cultured human CRC cells HCT116 and LoVo were assayed for their viability and migration using CCK-8 tests and transwell migration assays. The expression of EMT-specific markers (E-cadherin, N-cadherin and vimentin) was analyzed biochemically by RT-qPCR and immunoblot analyses. Interaction among LINC00586, LSD1, and ASXL1 was determined by RNA immunoprecipitation and chromatin immunoprecipitation. In vivo analysis of LINC00586 was performed in nude mice xenografted with HCT116 cells. LINC00586 was overexpressed in CRC tissues and associated with patient survival. LINC00586 knockdown repressed HCT116 and LoVo cell viability, migration, their phenotypic switch from epithelial to a mesenchymal, and tumorigenesis in vivo. We demonstrated LINC00586 recruited the LSD1 into the ASXL1 promoter region and epigenetically silenced the ASXL1 expression. An ASXL1 gene resisting to LINC00586 attack was demonstrated in cultured HCT116 and LoVo cells and mouse xenograft models of human CRC. Overall, discovery of the LINC00586/LSD1/ASXL1 axis partially explains epigenetic mechanism regulating EMT in CRC, providing a therapeutic target to limit CRC metastasis.